2015
DOI: 10.1016/j.immuni.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

PI3-Kinase-γ Has a Distinct and Essential Role in Lung-Specific Dendritic Cell Development

Abstract: Development of dendritic cells (DCs) commences in the bone marrow, from where pre-DCs migrate to peripheral organs to differentiate into mature DCs in situ. However, the factors that regulate organ-specific differentiation to give rise to tissue-specific DC subsets remain unclear. Here we show that the Ras-PI3Kγ-Akt-mTOR signaling axis acted downstream of FLT3L signaling and was required for development of lung CD103(+) DCs and, to a smaller extent, for lung CD11b(+) DCs, but not related DC populations in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…cDC1s – essential for preserving immune tolerance and mounting antiviral and antitumour responses 15 critically depend on the transcription factors Batf3, Irf8 and Id2 for their development 55 . Besides, additional factors have been identified that do not affect lymphoid tissue resident cDC1s homeostasis, but seem to have profound roles in the maintenance of peripheral tissue cDC1s, such as Csf2rb 25 , MycL 56 and PI3Kγ 57 . Here we add XBP1, a major transcription factor of the UPR to the growing list of regulators involved in the homeostasis of tissue-resident cDC1s.…”
Section: Discussionmentioning
confidence: 99%
“…cDC1s – essential for preserving immune tolerance and mounting antiviral and antitumour responses 15 critically depend on the transcription factors Batf3, Irf8 and Id2 for their development 55 . Besides, additional factors have been identified that do not affect lymphoid tissue resident cDC1s homeostasis, but seem to have profound roles in the maintenance of peripheral tissue cDC1s, such as Csf2rb 25 , MycL 56 and PI3Kγ 57 . Here we add XBP1, a major transcription factor of the UPR to the growing list of regulators involved in the homeostasis of tissue-resident cDC1s.…”
Section: Discussionmentioning
confidence: 99%
“…In this model inhibition of mTORC1 by rapamycin is able to reverse the defect conferred by Lamtor2 deletion. Recent evidence has implicated PI3Kγ upstream of mTORC 1 in the development of CD103 + DCs in the lungs (Nobs et al, 2015). …”
Section: Mtor In the Innate Immune Systemmentioning
confidence: 99%
“…Dendritic cells (DCs) are sentinel immune cells that develop from hematopoietic progenitors into functionally distinct subsets, including two types of conventional DCs (cDCs), cDC1 and cDC2, and plasmacytoid dendritic cells (pDC) . Fms‐related tyrosine kinase 3 ligand (Flt3L) induces DC differentiation and activates nutrient‐sensitive signaling pathways, including phosphoinositide 3‐kinase (PI3K)/mammalian target of rapamycin . Emerging evidence implicates the metabolic state of hematopoietic cells as a determinant of cell fate .…”
Section: Introductionmentioning
confidence: 99%